Mineralogy And Geology Of Texaco's Hobson Uranium Deposit, Karnes County, Texas - Harry M. Dahl; Christie A. Callender (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
The Hobson uranium deposit is located in Karnes County, Texas, along the prominent south Texas uranium trend. The uranium mineralization occurs in the Deweesville Sandstone of the Whitsett Formation of the Eocene Jackson Group. The host rock is a friable, fine-grained, well-sorted, highly porous and permeable sandstone interpreted to be an ancient beach deposit. The sandstone contains significant volcanic constituents and ranges in composition from arkosic to tuffaceous. Locally, the host sandstone contains hard, dense opal cement. Bentonitic shales underlie and overlie the mineralized sandstone unit. Geometrically, the Hobson uranium-bearing zone resembles an elongated roll front type deposit. Chemical uranium values compared with gamma ray equivalent uranium values indicate that the uranium has been dissolved from the updip side and precipitated on the down- dip side of the roll front. Details of the uranium mineralization were studied using thin section microscopy, autoradiography, x-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) techniques. The uranium mineralization occurs in the pores of the sandstone, as grain coatings and as replacement of sand-size and smaller grains. It is commonly associated with pyrite and other opaque minerals. Other favored hosts for uranium (other than pore openings) appear to be clay aggregates, altered rock and glass fragments, and carbonaceous plant debris. Aggregates of coffinite were identified by XRD and SEM/EDS analyses. Some uranium mineralization also appears to be dispersed and is postulated to be adsorbed on the clay and carbonaceous matter.